OP0095 Soluble cd163 as a potential biomarker in systemic sclerosis. (12th June 2018) - Frantz, C.; Pezet, S.; Avouac, J.; Allanore, Y.
Abstract : Background: Recent accumulating evidences indicate a crucial role of macrophage lineage in the pathogenesis of fibrotic diseases including systemic sclerosis (SSc). CD163 is a surface marker expressed by M2 macrophages that accumulate during the healing phase of acute inflammation. It is actively released from the plasma membrane in response to certain inflammatory stimuli and enters the circulation in its soluble form (sCD163). Objectives: In this study, we aimed to evaluate the performance of serum and urinary sCD163 concentrations as possible biomarker in SSc. Methods: Urine and serum samples were obtained from SSc patients, fulfilling the 2013 ACR/EULAR classification criteria for SSc, and age- and sex-matched controls. Serum and urinary sCD163 concentrations were measured by commercially available ELISA kit (R and D systems) and evaluated for their significance as potential biomarkers. Statistical analysis was carried out using Mann-Whitney U test and the relationship between parameters was statistically examined by Spearman's rank test. Results: Two hundred and three SSc patients were included, 163 (80%) were female, with a mean ±standard deviation (SD) age of 59±13 years and a mean ±SD disease duration of 12±9 years. Eighty-one (41%) patients had diffuse cutaneous SSc and mean ±SD mRSS was 6.6±7.7. Lung fibrosis on imaging was observed in 33% of the patients, 7% had pulmonary arterial hypertension, 44% had history of digital ulcers and 41% were taking immunosuppressive therapy. Control group consisted of 47 age- and sex-matched patients with non-inflammatory diseases, being osteoporosis for the very large majority. Serum sCD163 levels were significantly higher in SSc patients compared with controls (mean ±SD: 529±251 vs 385.1±153 ng/ml; p<0.001). Urinary sCD163 concentrations in SSc patients were also higher than those in controls, but this did not reach significance (236.9±498 vs 176.2±173 ng/mg uCr; p=0.580). When looking at the subsets according to skin disease or disease duration, no difference could be identified. Furthermore, when the organ involvements were investigated, no subpopulation could be identified as having higher concentrations. Conclusions: To our knowledge this is the first evaluation of both serum and urinary sCD163 levels in SSc. Our results show a significant difference for sera values that should be prioritised for further studies as compared to urinary concentrations conversely to what has been described in lupus. Our results further support that the M2 macrophages/CD163 signalling system may play a role in the pathogenesis of SSc. However, further studies are required to address the exact role of CD163 in the pathogenesis of SSc and to determine whether it could help in the risk-stratification of the patients in this heterogeneous disease. Disclosure of Interest: None declared